Why have candidates in Indonesian elections increasingly been rallying ethnic and religious support? - FOX, Colm A. (Institutional Knowledge at Singapore Management University, 2020)
Ethnicity and religion often become politicised in elections. Research has found that this is particularly true during a transition to democracy. During these times, fragile democratic rules and practices, coupled with strong ethnic bonds, often motivate aspiring politicians to bolster their support by appealing to voters’ emotional allegiances to their tribe, ethnicity, or religion. But, Indonesia’s case is puzzling.